Overcoming Barriers in Oncolytic Virotherapy with HDAC Inhibitors and Immune Checkpoint Blockade - Marchini, Antonio (Viruses, 2016)
Oncolytic viruses (OVs) target and destroy cancer cells while sparing their normal counterparts. These viruses have been evaluated in numerous studies at both pre-clinical and clinical levels and the recent Food and Drug Administration (FDA) approval of an oncolytic herpesvirus-based treatment raises optimism that OVs will become a therapeutic option for cancer patients. However, to improve clinical outcome, there is a need to increase OV efficacy. In addition to killing cancer cells directly through lysis, OVs can stimulate the induction of anti-tumour immune responses. The host immune system thus represents a “double-edged sword” for oncolytic virotherapy: on the one hand, a robust anti-viral response will limit OV replication and spread; on the other hand, the immune-mediated component of OV therapy may be its most important anti-cancer mechanism. Although the relative contribution of direct viral oncolysis and indirect, immune-mediated oncosuppression to overall OV efficacy is unclear, it is likely that an initial period of vigorous OV multiplication and lytic activity will most optimally set the stage for subsequent adaptive anti-tumour immunity. In this review, we consider the use of histone deacetylase (HDAC) inhibitors as a means of boosting virus replication and lessening the negative impact of innate immunity on the direct oncolytic effect. We also discuss an alternative approach, aimed at potentiating OV-elicited anti-tumour immunity through the blockade of immune checkpoints. We conclude by proposing a two-phase combinatorial strategy in which initial OV replication and spread is maximised through transient HDAC inhibition, with anti-tumour immune responses subsequently enhanced by immune checkpoint blockade.